Identification and Characterization of Wheat Yellow Striate Virus, a Novel Leafhopper-Transmitted Nucleorhabdovirus Infecting Wheat - Liu, Yan; Du, Zhenzhen; Wang, Hui; Zhang, Song; Cao, Mengji; Wang, Xifeng (Frontiers in Microbiology, 2018)
A new wheat viral disease exhibiting unusual symptoms - yellow stripes on leaves and slight dwarfism -was found in China. The bullet-shaped viral particles within the nucleus of the infected wheat leave cells, which possessed 180-210 nm length and 35-40 nm width, were observed under transmission electron microscopy. The putative wheat-infecting rhabdovirus vectored by the leafhopper Psammotettix alienus was tentatively named wheat yellow striate virus (WYSV). The full-length nucleotide sequence of WYSV was determined using transcriptome sequencing and RACE analysis of both wheat samples and leafhoppers P. alienus. The negative-sense RNA genome of WYSV contains 14,486 nucleotides (nt) and seven open reading frames (ORFs) encode deduced proteins in the order N-P-P3-M-P6-G-L on the antisense strand. In addition, WYSV genome has a 76-nt 3′ leader RNA and a 258-nt 5′ trailer, and the ORFs are separated by conserved intergenic sequences. The entire genome sequence shares 58.1% and 57.7% nucleotide sequence identity with two strains of rice yellow stunt virus (RYSV-A and RYSV-B) genomes, respectively. The highest amino acid sequence identity was 63.8% between the L proteins of the WYSV and RYSV-B, but the lowest was 29.5% between the P6 proteins. Phylogenetic analysis firmly established WYSV as a member of the genus Nucleorhabdovirus. Collectively, this study provided evidence that WYSV is likely the first nucleorhabdovirus described infecting wheat via leafhopper P. alienus transmission.